Advocating causal analyses of media and social change by way of social mechanisms. (1st June 2019) - Helle-Valle, Jo
Studies of (new) media and social change should strive to introduce causality into the analysis. Studies relying on quantitative data tend to provide either too simplistic explanations or just point to correlations while qualitatively based studies tend to be so particularistic that the potential for generalizing findings from specific cases is negligible. In this article, it is argued that proper accounts should strive to suggest causal connections between social change and media practices – not by resorting to unrealistic cover law-explanations but by identifying and analysing social mechanisms. Done properly, such analyses would: heed acting subjects; explain these practices through expositions of the minute steps that link A and B; and be realistic accounts – both in the sense of being based on 'thick' descriptions and of being easily recognizable when compared to what is actually happening in everyday life.